I am the light of this world : a novel - Parker, Michael, 1959- (Algonquin Books of Chapel Hill, 2022)
"In the early 1970s, in Stovall, Texas, seventeen-year-old Earl--a loner, dreamer, lover of music and words--meets Tina, the new girl in town. Tina convinces Earl to drive her to see her mother in Austin, where Earl and Tina are quickly separated. Two days later, Earl is being questioned by the police about Tina's disappearance and the blood in the trunk of his car. But Earl can't remember what happened in Austin, and with little financial support from his working-class family, he is sentenced for a crime he did not commit. Forty years later, Earl is released into a world he can barely navigate. Settling in a small town on the Oregon coast, he attempts to establish a sense of freedom from both bars and razor wire and the emotional toll of incarceration. But just as Earl finds the rhythm he's always sought, his past returns to endanger the new life he's built"--Book jacket flap.